Developing News Item Instructional Media with Authentic Material Using SAC to Enhance Students’ Reading Ability - Lusiana Sari, Andini; Rudi Hartono; Sri Wahyuni (English Education Journal, 2024)
The rapid advancement of technology has led to the incorporation of technology in teaching and learning processes. One way to achieve this is through smartphone-based media, such as Smart Apps Creator (SAC), which creates simple mobile applications for improving teaching and learning activities. During learning process of EFL, researchers found problems especially in learning reading. The problems are students’ lack of motivation in reading and students’ difficulties in dealing with reading comprehension. This study aims to develop a simple mobile application as an instructional media for teaching News Item text with authentic materials for phase F students in grade 12th, and to test its effectiveness focusing on improving students' reading ability. The study also examines the potential of utilizing smartphones to support reading instruction, overcome students’ problem in reading, and encourage a more lively and effective learning environment. The product specifications include a mobile app that performs as an instructional media, containing News Item text enriched with authentic materials and is user-friendly. The study applied Borg and Gall (1983) model of educational research and development since the model includes a methodical process that the researchers can follow to guarantee that the final product satisfies behaviorally defined goals and complies with appropriateness standards. Data collection was conducted in SMAN 1 Kradenan Kabupaten Grobogan, with 29 students from grade 12th participating in field testing to evaluate the usability and effectivity of the apps to be used in learning. The result showed that the apps being developed is highly feasible to be used in learning and is effective in enhancing students’ reading ability.